1311. Intrapulmonary Pharmacokinetics of Cefiderocol in Hospitalized and Ventilated Patients Receiving Standard of Care Antibiotics for Bacterial Pneumonia. (31st December 2020) - Katsube, Takayuki; Wajima, Toshihiro; Echols, Roger; Portsmouth, Simon; Ariyasu, Mari; Rodvold, Keith; Nicolau, David P
Abstract: Background: Cefiderocol (CFDC), a novel siderophore cephalosporin, has potent in vitro activity against Gram-negative bacteria causing nosocomial pneumonia (NP). The non-inferiority of CFDC to meropenem in Day 14 all-cause mortality in NP was previously demonstrated. In this study, we assessed the intrapulmonary pharmacokinetics of CFDC in hospitalized and ventilated patients with bacterial pneumonia receiving standard of care (SOC) antibiotics. Methods: A multicenter, single-arm, open-label study was conducted to assess epithelial lining fluid (ELF) and plasma concentrations of CFDC at steady state in mechanically ventilated patients with bacterial pneumonia receiving SOC antibiotics (NCT03862040). Seven patients received 2 g doses of CFDC (or renally adjusted doses), infused over 3 hours, q8h, or q6h for patients with augmented renal function (creatinine clearance estimated by Cockcroft-Gault equation >120 mL/min). One bronchoalveolar lavage (BAL) sample per patient was collected to determine ELF concentration at 3 or 5 hours after at least 3 CFDC doses (or ≥6 doses in patients with severe renal impairment). Four blood samples were collected per patient for plasma concentrations at 1, 3, 5, and 7 hours after the start of the infusion used for BAL sampling. Urea concentrations in blood and BAL were measured to calculate CFDC concentrations in ELF. Results: Geometric mean (minimum, maximum) ELF concentration of CFDC was 7.63 (3.10, 20.7) µg/mL at the end of infusion (3 h after the start of infusion) (N=4) and 10.4 (7.19, 15.9) µg/mL at 2 hours after the end of infusion (5 h after the start of infusion) (N=3). ELF/free plasma concentration ratios were estimated to be 0.212 at the end of infusion and 0.547 at 2 hours after the end of infusion based on the in vitro unbound fraction of 0.422. Conclusion: The individual ELF concentrations of CFDC were close to, or higher than, 4 µg/mL in pneumonia patients. Compared with the ELF/free plasma area under the curve ratio in healthy subjects (0.239), the ELF/free plasma concentration ratio at the end of infusion (0.212) was comparable, and at 2 hours after the end of infusion (0.422) was higher in pneumonia patients. These findings suggest delayed distribution and sustained exposure of CFDC in the ELF of pneumonia patients. Disclosures: Takayuki Katsube, PhD, Shionogi & Co., Ltd. (Employee) Toshihiro Wajima, PhD, Shionogi & Co., Ltd. (Employee) Roger Echols, MD, Shionogi Inc. (Consultant) Simon Portsmouth, MD, Shionogi Inc. (Employee) Mari Ariyasu, BPharm, Shionogi & Co., Ltd. (Employee) Keith Rodvold, PharmD, FCCP, FIDSA, Shionogi Inc. (Consultant) David P. Nicolau, PharmD, Cepheid (Other Financial or Material Support, Consultant, speaker bureau member or has received research support.)Merck & Co., Inc. (Consultant, Grant/Research Support, Speaker's Bureau)Wockhardt (Grant/Research Support)